2005
DOI: 10.1128/jcm.43.8.3932-3937.2005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factora-2anda-8Microsatellite Alleles with Human Papillomavirus and Squamous Intraepithelial Lesions among Women in Brazil

Abstract: Infection with oncogenic human papillomavirus (HPV) is considered to be the major risk factor for cervical cancer. Tumor necrosis factor (TNF) is a pluripotent cytokine that plays an important role in inhibiting the action of microbial agents, and TNF microsatellite polymorphisms have been associated with several diseases, including cancer and viral infections. This study analyzed the associations between TNFa to -e microsatellite polymorphisms and the severity of squamous intraepithelial lesions (SIL), accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Other studies noted that infection with HR or other aggressive genotypes of HPV gave rise to transformed cells that were resistant to TNFα-mediated growth inhibition; this outcome seemed to be due to a decreased expression/loss of the TNFα receptors on the infected cells (Simoes et al, 2005;Govan et al, 2006). In contrast, Song et al (2007) reported that TNFα and IL-10 levels did not correlate with pre-cancerous lesions of the cervix after HPV infection.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Other studies noted that infection with HR or other aggressive genotypes of HPV gave rise to transformed cells that were resistant to TNFα-mediated growth inhibition; this outcome seemed to be due to a decreased expression/loss of the TNFα receptors on the infected cells (Simoes et al, 2005;Govan et al, 2006). In contrast, Song et al (2007) reported that TNFα and IL-10 levels did not correlate with pre-cancerous lesions of the cervix after HPV infection.…”
Section: Discussionmentioning
confidence: 77%
“…Tumor necrosis factor (TNF)-α, which plays a key role in viral clearance and inflammatory reactions after viral infections and cancer (and as such is considered as proinflammatory cytokine), is secreted by several cell types including macrophages and T-lymphocytes (Simoes et al, 2005). In addition, TNFα has anti-tumor properties and is spontaneously released by HPV-infected cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 117 potentially individual abstracts were found from the the Pubmed, Embase, Web of Science, and Wanfang databases, but only 24 studies were preliminarily identified and were further assessed for inclusion [13][25], [30][39] (Figure 1). After reviewing the full-texts of those 25 studies, three studies were excluded for irrelevant studies [36], [37], [39] and two were excluded for studies assessing the other TNF gene polymorphisms [35], [38].…”
Section: Resultsmentioning
confidence: 99%
“…43 This may in part be due to the reduction of E-cadherin-mediated interactions between keratinocytes and Langerhans cells. 44 As a result, cytokine production is altered, [46][47][48] and the virus is not cleared by the cell-mediated immune system.…”
Section: Etiology and Pathogenesismentioning
confidence: 98%